Surgical Outcome of Modified Karydakis Flap and Modified Limberg Flab in the Management of Sacroccygeal Pilonidal Disease: A Comparative Study - Baz, Yasser; Orban, Yasser Ali; Ezzat, Mohamed Mahmoud (Journal of Coloproctology, 2022)
Introduction Sacrococcygeal pilonidal disease (SPD) is a chronic suppurative condition of the sacrococcygeal region causing chronic sinus tract or cyst. It is an acquired complex disease more common in young adult males, causing considerable morbidity and long periods of interruption in work or education. From simple conservative techniques to complex flap reconstruction, many debatable treatment options are offered; however clear dynamics toward the widespread use of minimally invasive methods and off-midline flap reconstruction are suggested in all guidelines, which recommend the Karydakis and Limberg flap modification. The plethora of literature compares procedures for identification of a single best treatment approach, which has proven to be difficult. The surgical outcome of both techniques is compared in the present study.Objective To compare the surgical outcomes of the modified Karydakis flap (MKF) versus the modified Limberg flap (MLF) in SPD.Materials and Methods The present study was conducted at the general surgery department on SPD patients who were ≥18 years old. A total of 67 participants were included after obtaining the informed consent, with group A comprising 33 patients undergoing the MLF procedure and group B comprising 34 patients undergoing the MKF procedure.Results The mean patient age was 28.85 (range, 18–44) years old. For the MKF and MLF methods, the average operating duration was 32.5 (range, 25–40) and 54.5 (range, 45–65) minutes, respectively. The MKF approach was found to significantly improve pain score, mean sitting painless time, return to normal activity, wound healing time, and patient satisfaction.Conclusion Comparative outcomes were seen between both MKF and MLF; however, our findings show that MKF is a more favourable method than MLF with superior outcomes.
Keywords: modified karydakis; limberg flap; pilonidal sinus